Papel do receptor TRPV1 em um modelo articular de gota aguda em ratos - Hoffmeister, Carin Gorete Hendges (2014)
The gout is an extremely painful type of arthritis. Despite the large number of drugs available for its treatment, they usually cause many adverse effects that limit their use. Then, further investigations are necessary for a better understanding the different mechanisms involved in gout. It was found previously that TRPV1 receptor, an ion channel modulated by various inflammatory mediators mediated edema and the nociceptive responses induced by subcutaneous injection of MSU in rats. In this plantar model, activation of TRPV1 depended largely on the activation of mast cells. Since the environments articular broadly differ as their cellular constituents, questioned the involvement of this receptor in a more reliable model with this clinical arthropathy. The aim of this study was to investigate the role of TRPV1 in a model of acute gout induced by intra-articular administration (i.a.) of crystals of monosodium urate (MSU) tíbio-tarsal articulation rats. It was observed that the antagonism of the TRPV1 receptor (by the selective antagonist SB366791), systemic knockdown (caused by treatment with resiniferatoxin subcutaneous injection a TRPV1 agonist) or axonal silencing (perineural injection a combination of capsaicin and QX-314) sensory fibers TRPV1-positive significantly prevented the pain-related behaviors (spontaneous nociception, heat hyperalgesia, and mechanical allodynia) and inflammation (edema, plasma extravasation, leukocyte infiltration and IL - 1β ) was caused by the administration of MSU. Additionally, we observed a significant increase in immunoreactivity of TRPV1 in articular tissue 4 hours after administration of MSU. Subsequently, we investigated the possibility role of NO, an endogenous activator of TRPV1 in this model. The administration of MSU induced an increase in the production of stable metabolites (NOx) emissions of nitric oxide (NO) exudates in the joint, which was inhibited by a selective inhibitor of nitric oxide synthase (NOS). In addition, the non-selective NOS inhibitor prevented the spontaneous nociception, edema and plasma extravasation, and leukocyte infiltration after MSU injection. Moreover it was found that the administration of a NO donor induced heat hyperalgesia and spontaneous nociception, but not mechanical allodynia and edema. The TRPV1 receptor antagonism prevented only the edema caused by that donor. Thus, these results suggest that TRPV1 plays a role in the development and maintenance of nociceptive and inflammatory responses triggered in the model of acute articular gout, but only edematogenic response appears to be mediated by TRPV1 activation by NO.